Influence of the humanitarian environment on improving the quality of training of specialists in a technical university - О. G. Savka (Российский технологический журнал, 2021)
The article is devoted to the consideration of the theoretical aspects of the influence of the organization of the humanitarian environment in a technical educational institution on improving the quality of training specialists, increasing their competitiveness in the labor market. The analysis of special literature and generalization of different points of view on the subject of research act as research methods. The humanitarian environment represents a certain content orientation of the educational system of curricula and work programs of disciplines that include the unity of material and spiritual values that are responsible for the formation of students’ personality. Each teacher considers this problem in his own way, so the points of view have their own specifics. The humanitarian environment of the university includes a specially organized training system in which a set of specially selected methods and technologies is used to «nurture» a competitive specialist with a set of not only professional, but also personal competencies. The training of specialists in a technical university has its own characteristics related to the further professional implementation of graduates. Students at the stage of training must master special competencies, develop personal qualities, be motivated to study disciplines and master new types of activities. The organization of the humanitarian environment in the organization should be implemented at all levels: university, faculty, at each specific lesson in the study of disciplines, both provided for in the curriculum and extracurricular according to the plan of educational work. For this purpose, it is necessary to maintain and control the interaction of students with all components of the educational environment of a higher educational institution using methods such as: humanitarian technologies, mentoring, organizing a positive psychological climate in the institution, introducing additional educational programs, using active and innovative teaching methods.